Can the application of low doses of glyphosate induce the hormesis effect in upland rice? - Ferrari, Samuel [UNESP]; Marsala, Leonardo [UNESP]; Oliveira Cunha, Matheus Luís [UNESP]; dos Santos Cordeiro, Luis Fernando [UNESP]; Tropaldi, Leandro [UNESP]; de Mattos Barretto, Vitor Corrêa [UNESP]; Alves de Oliveira, Lara Caroline [UNESP] (Taylor & Francis, 2021)
The aim of this research was to verify the effect of glyphosate low doses on leaf macronutrient levels and vegetative traits of upland rice in two growth stages. The treatments were arranged in 2 × 6 factorial scheme. The first factor consisted of applications in two growth stages of rice crop (tillering and floral differentiation) and the second factor was the low doses of glyphosate (0, 10, 20, 40, 70 and 100 g e.a. ha−1). In full bloom, the chlorophyll content was determined in a sample of 30 flag leaves. In these leaves, the contents of macronutrients were determined. At the maturity of the rice plant, the stem count was performed per m2, effective tiller and the plant height was measured. The low doses did not influence the leaf content of macronutrients. The plant height was reduced with an increase in the low doses of glyphosate, having a greater effect on the floral differentiation stage. When applied low doses of glyphosate at the floral differentiation stage, chlorophyll content increases and when applied to tillering there is a linear decrease in chlorophyll content. The number of stems increases with the application of low doses at floral differentiation.
Keywords: macronutrients; Oryza sativa L; vegetative components